2017
DOI: 10.1016/j.canep.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of malignant peritoneal mesothelioma: A population-based study

Abstract: Our study indicates that MPeM in Finland is rare and fatal, which is in accordance with previous reports from other countries. MPeM is also a fatal disease, since most of the patients died due to MPeM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
(34 reference statements)
0
17
0
4
Order By: Relevance
“…14 Their classification scheme was similar to the categorical analysis of PCI applied in this study. They considered PCI Score as the "T" component in their TNM staging system and divided PCI into four categories: T1 (0-10), T2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), T3 (21-30) and T4 (31-39). 14 Magge et al have studied prognostic factors of MPeM and applied the Dutch simplified peritoneal cancer index (SPCI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Their classification scheme was similar to the categorical analysis of PCI applied in this study. They considered PCI Score as the "T" component in their TNM staging system and divided PCI into four categories: T1 (0-10), T2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), T3 (21-30) and T4 (31-39). 14 Magge et al have studied prognostic factors of MPeM and applied the Dutch simplified peritoneal cancer index (SPCI).…”
Section: Discussionmentioning
confidence: 99%
“…Ascites is a common radiographic finding and was observed in 79.2% of the patients. 21 While the median survival of patients with ascites was 7 months-compared to 39-months in patients without ascites-this result was not 13 Novel nomogram for 3-and 5-year overall survival 2014 Magge et al 12 The Dutch simplified peritoneal cancer index (SPCI)…”
Section: Discussionmentioning
confidence: 99%
“…Although an increasing percentage of patients receive anti-cancer therapy, the majority of The patient characteristics found in this study are comparable with those described in earlier reports. [9][10][11][12][13][14] Women with MPM live longer than men with MPM. It is sometimes suggested that the better survival among women is caused by a misdiagnosis of MPM because it has similarities to ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Das diffuse maligne peritoneale Mesotheliom (DMPM) ist eine seltene Erkrankung, die häufiger bei Männern als bei Frauen vorkommt, wobei Überlebenszeiten von 4-13 Monaten berichtet wurden [1][2][3][4][5].…”
Section: Introductionunclassified